The relationship between novel inflammatory markers SII, SIRI, MHR, UHR and insulin resistance in patients with type 2 diabetes: based on a retrospective analysis - He, Rongrong; Sun, Hui; Liu, Haiying; Li, Jinxia (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to investigate the relationship between newly identified inflammatory indicators and IR in patients with T2DM, thereby providing a reference basis for the early clinical prevention, diagnosis, and treatment of IR in patients with T2DM.MethodsA total of 779 patients with T2DM admitted to the Endocrinology Department of our hospital from January 2022 to December 2024 were included in the observation group. Five hundred healthy individuals who underwent physical examinations during the same period were randomly selected as the control group. Patients in the observation group were divided into the IS group, the EIR group, and the SIR according to the HOMA-IR level. Analyze the relationship between the four indicators and IR in patients with T2DM, and observe whether they are independent risk factors for IR in T2DM patients, as well as analyze their clinical utility.ResultsCompared with the control group, the levels of inflammatory indicators SII, SIRI, MHR and UHR in the observation group were significantly increased. The levels of SII, SIRI, MHR and UHR in the EIR group and the SIR Group were significantly higher than those in the IS group. Moreover, with the increase in HOMA-IR score, all four inflammatory indicators showed an upward trend. The results of Spearman’s rank correlation analysis showed that all four indicators were positively correlated with IR in patients with T2DM. Multivariate ordered logistic regression analysis showed that all four indicators were independent risk factors for IR in patients with T2DM. The ROC results indicated that SII, SIRI, MHR and UHR could serve as potential discriminatory ability indicators for evaluating the degree of IR in patients with T2DM.ConclusionThe levels of SIRI, SII, UHR and MHR in patients with T2DM increase and are positively correlated with IR. They are independent risk factors for IR in patients with T2DM and have clinical utility to a certain extent. They can provide a reference basis for the early clinical prevention, diagnosis and treatment of IR in patients with T2DM.